Decentering and recentering the writing centre using online feedback: Towards a collaborative model of integrating academic literacies development - Collett, Karen Suzette; Dison, Arona (Stellenbosch Papers in Linguistics Plus, 2019)
Since its inception in 1994, the University of the Western Cape’s Writing Centre has been on the margins, viewed as an add-on to central learning and teaching activities at the university (Archer and Richards 2011, Clarence 2011). In this article, we use the constructs of place, space, and power to explore the decentering of feedback on students’ writing from the face-to-face, physical location of the Centre to the formative assessment space in a module. We reflect on the Centre’s engagement with a formative online feedback intervention conducted by a lecturer within a Bachelor of Education Honours course. Writing centre tutors participated in providing formative feedback on nested, scaffolded tasks leading to a long essay, using the feedback function of the Turnitin platform. The space of engagement with students moved from the face-to-face, physical writing centre location to the online space. We found that the development of the academic writing and feedback literacies of writing tutors, students, and the lecturer were developed through sustained and responsive online and face-to-face communities of praxis. In this process, there was a partial decentering and recentering of the role of the Centre, enabled by technology and the integration of the development of academic literacies within the course curriculum. The sustained engagement between the lecturer, tutors, and writing centre coordinator played an essential role in the effectiveness of the intervention. However, in order to further develop the feedback literacies of students, the online feedback needs to be complemented with additional face-to-face interaction. We argue for both a decentering and recentering of the role of writing centres towards supporting departments in the integration of academic literacies development into curricula. One of the ways of doing this is by using technology to expand capacity in order to give students feedback on their writing within a blended learning environment that focuses on formative assessment.